Accessibility to ICTs in Costa Rica: A Disruptive Change in the Mind of the Costa Rican Society - Ríos Navarro, Darío (2017)
The present paper analyzes the definition of the concept of universal accessibility, considering the current state of accessibility in Costa Rica, especially in the field of technology. It aims to raise awareness and provide guidance to the public reader, pointing out some of the myths present within the definition of accessibility, taking into account different perspectives from other studies, and exemplifying situations related to web accessibility, mainly. We analyze the data generated by the National Statistics and Census Institute (INEC) on the population with disabilities in Costa Rica. This analysis is done through statistical information provided by the past censuses carried out during the decades of the present century, considering the importance of improving ICTs for people who have some type of disability, caused by nature or by time. The paper reviews different projects that, at present, are being promoted in ICTs and are considered important advances to improve the conditions of people with disabilities.  It promotes the inherent need to work on the development of ICTs in Costa Rica from different frameworks. In the political and legal frameworks, it identifies the need to extend the rules promoting the laws in favor of disability in the country. In conclusion, the article analyzes that Costa Rica could become one of the first countries in Central America and the Caribbean covering the needs of people with disabilities, through the strengthening and recognition of ICTs that give added value to build a universal accessibility.